The Archaeologist In-Between Olov Janse, 1892-1985 - Källén, Anna (Kriterium, 2021)
Olov Janse was an archaeologist with a remarkable life. From his birth in Sweden 1892 to his death in the United States 1985, he travelled several times across the world and was present in some of the most important episodes of 20th century world history. His works and networks connected museums and political institutions in Sweden, France, Vietnam and the United States: from the Swedish History Museum, the Museum of Far Easter Antiquities, the French Musée d'antiquites nationales, the Cernuchi museum, and the French research institute EFEO in Hanoi, to UNESCO, the Harvard Peabody Museum, the Smithsonian Institution, and the U.S. Department of State. He left behind artefacts and documents in museum collections and archives across the world. But his name is largely unknown, and his most important contributions - the connection of people and ideas between continents and contexts - have remained invisible in historical accounts of all these institutions. He was, in every sense, an archaeologist in-between. This book follows in the footsteps of Olov Janse and his wife Renée, as they move between continents and contexts, connecting key actors and institutions in social and professional networks across the world. It tells the formidable story of an archaeologist navigating through world politics, from a late 19th century industrial town in Sweden, to early 20th century Parisian museums, to French Indochina and the Philippines in the 1930s, to the formation of UNESCO in 1946, and ending with public diplomacy for the U.S. Department of State at the verge of the Vietnam War.